An exploratory study of user resistance in healthcare IT. (30th July 2014) - Ngafeeson, Madison N.; Midha, Vishal
The US healthcare system is clearly experiencing a major transition. By 2015, the healthcare sector is expected to have migrated from a paper record system to a completely electronic health record (EHR) system. The adoption and use of these systems are expected to increase legibility, reduce costs, limit medical errors and improve the overall quality of healthcare. Hence, the US government is investing $70 billion over a 10-year period to facilitate the transition to an electronic system. However, early reports show that physicians and nurses among other health professionals continue to resist the full use of the system. This paper uses the theory of cognitive dissonance to investigate user resistance in HIT. It builds on a